2016
DOI: 10.1093/jmt/thw004
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Music Therapy for Chronic Pain Management in Inner-City African Americans: A Mixed Methods Feasibility Study

Abstract: Background To date, research on music for pain management has focused primarily on listening to pre-recorded music for acute pain. Research is needed on the impact of active music therapy interventions on chronic pain management. Objective The aim of this mixed methods research study was to determine feasibility and estimates of effect of vocal music therapy for chronic pain management. Methods Fifty-five inner city adults, predominantly African-Americans, with chronic pain were randomized to an 8-week voc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 37 publications
2
62
1
8
Order By: Relevance
“…The effects of singing on pain interference were examined in seven quantitative studies with 205 participants (Bradt, ; Fogg‐Rogers et al, ; Grape et al, ; Kenny & Faunce, ; Morrison et al, ; Pongan et al, ; Stegemoller, ). These studies utilized pain questionnaires, which asked the degrees of pain interference in a numerical scale: for example, “Mark the box beside the number that describes how, during the past 24 hr, pain has interfered with your general activity, normal work, etc.," (BPI).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of singing on pain interference were examined in seven quantitative studies with 205 participants (Bradt, ; Fogg‐Rogers et al, ; Grape et al, ; Kenny & Faunce, ; Morrison et al, ; Pongan et al, ; Stegemoller, ). These studies utilized pain questionnaires, which asked the degrees of pain interference in a numerical scale: for example, “Mark the box beside the number that describes how, during the past 24 hr, pain has interfered with your general activity, normal work, etc.," (BPI).…”
Section: Resultsmentioning
confidence: 99%
“…These studies utilized pain questionnaires, which asked the degrees of pain interference in a numerical scale: for example, “Mark the box beside the number that describes how, during the past 24 hr, pain has interfered with your general activity, normal work, etc.," (BPI). Pain interference decreased from pre‐ to post‐singing intervention in studies with chronic pain patients (Bradt, ), people with Parkinson's (Stegemoeller, ), people with COPD (Morrison et al, ) and people with irritable bowel syndrome (IBS) (Grape et al, ); however, the decrease was only significant in Bradt et al () . Four RCTs yield mixed results: Bradt et al () and Grape et al () studies, rated as of less than good quality, reported findings that “significantly favours intervention,” whereas Pongan et al () findings “significantly favours control” and Kenny's () had a “trend towards control.” Pongan's study () was appraised to be of good quality, whereas Kenny's study () had a number of weaknesses, such as a high attrition rate (only 31% of singing group participants completed the 3‐week long singing programme) and not reporting missing data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A hallmark of human movement is volitional control the freedom to shift easily, automatically, and securely within the changing requirements of daily living (Batson et al, 2016). Vocal music therapy may be effectual in building necessary stepping-stones for effectual chronic pain management, in other words strengthened self-efficacy, motivation, empowerment, and social engagement (Bradt et al, 2016). Music decreases the anxiety and pain scores of patients during SWL and is associated with higher satisfaction scores for remedies (Akbas et al, 2016).…”
Section: Resultsmentioning
confidence: 99%